Recurrent breast carcinoma presenting as postmenopausal vaginal bleeding: A case report - Binstock, Anna (Gynecol Oncol Rep, 2013)
• We discuss the recurrence of breast carcinoma presenting as postmenopausal vaginal bleeding in a patient on Tamoxifen therapy. • Case report illustrates widespread genital tract manifestation of recurrent disease at time of presentation and rapid disease progression. • Discusses the importance of maintaining broad differential in diagnosis of postmenopausal vaginal bleeding.